Asymmetric auxin distribution establishes a contrasting pattern of aerenchyma formation in the nodal roots of Zea nicaraguensis during gravistimulation - Ning, Jiayang; Yamauchi, Takaki; Takahashi, Hirokazu; Omori, Fumie; Mano, Yoshiro; Nakazono, Mikio (Frontiers in Plant Science, 2023)
Auxin distribution is essential for determining root developmental patterns. The formation of lateral roots and constitutive aerenchyma, which is a gas space developed through cell death, is regulated by auxin in rice (Oryza sativa). However, it is unclear whether the involvement of auxin in constitutive aerenchyma formation is conserved in other species. In this study, we found that constitutive aerenchyma formation was regulated by auxin in the nodal roots of Zea nicaraguensis, a wild relative of maize (Zea mays ssp. mays) grown naturally on frequently flooded coastal plains. Subsequent gravistimulation (root rotation) experiments showed opposite patterns of aerenchyma and lateral root formation. Lateral root formation on the convex side of rotated roots is known to be stimulated by a transient increase in auxin level in the pericycle. We found that aerenchyma formation was accelerated in the cortex on the concave side of the rotated nodal roots of Z. nicaraguensis. A cortex-specific expression analysis of auxin-responsive genes suggested that the auxin level was higher on the concave side than on the convex side. These results suggest that asymmetric auxin distribution underlies the regulation of aerenchyma and lateral root formation in the nodal roots of Z. nicaraguensis. As aerenchyma reduces the respiratory cost of the roots, constitutive aerenchyma on the concave side of the nodal root may balance resource allocation, thereby contributing to the uptake of water and nutrients by newly formed lateral roots. Our study provides insights into auxin-dependent asymmetric root patterning such as that of gravistimulation and hydropatterning response.